On Convergence Results for Lipschitz Pseudocontractive Mappings - Shin Min Kang; Arif Rafiq (Journal of Applied Mathematics)
We establish the strong convergence for the Ishikawa iteration scheme associated with Lipschitz pseudocontractive mappings in real Banach spaces. Moreover, our technique of proofs is of independent interest.